STRATEGI PENGEMBANGAN BADAN USAHA MILIK DESA DI DESA MONCOBALANG KECAMATAN BAROMBONG KABUPATEN GOWA - Ardianti, Amelia; Razak, Andi Rozdianti; Andriana, Andriana (Universitas Muhammadiyah Makassar, 2022)
ABSTRACTThis study purposed to find out the Development Strategy of BUMDes in Moncobalang Village, Barombong District, Gowa Regency. This study used qualitative research and the type of research used descriptive. Data collection techniques used, interviews, observations and literature studies. The data was analyzed interactively which took place continuously until it was complete until the data obtained was saturated. The results showed that the BUMDes development strategy in Moncobalang Village which was analyzed using the strategic concept of Salusu that had been run well, the Vision and Mission to be achieved were in accordance with the program being run. But there were still some obstacles that occured such as the lack of utilization of natural resources in Moncobalang Village. In order for the BUMDes program had run well, the resource strategy prioritized in providing appropriate training to the community and also increasing the use of natural resources. Keywords: Strategy Concept, BUMDes Program.